1980
DOI: 10.1080/14640748008401168
|View full text |Cite
|
Sign up to set email alerts
|

A Simultaneous Shift in Apparent Direction: Further Evidence for a “Distribution-Shift” Model of Direction Coding

Abstract: When two superimposed moving dot fields are presented simultaneously, their axes of movement appear shifted away from each other. The shift only occurs when the two directions are within 90° of each other, and is directly comparable to that which results from adapting to one and testing on the other direction. This effect is taken as further evidence for a distribution-shift model in the direction domain. It is argued that the currently accepted model of movement detection, which restricts itself to comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 11 publications
10
78
0
Order By: Relevance
“…However, it is also of interest that displacements of one movement direction by another have been described by Mather and Moulden (1980). They found that if two superimposed fields of moving dots were observed simultaneously, their directions of movement were shifted away from each other.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also of interest that displacements of one movement direction by another have been described by Mather and Moulden (1980). They found that if two superimposed fields of moving dots were observed simultaneously, their directions of movement were shifted away from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of repulsive effects can also be observed in judgements between two transparently moving stimuli [1]. While these effects have been framed in terms of inhibitory interactions between directionally selective neurons as a low-level, sensory phenomenon (see [1][2][3][4]), it has also been suggested they could result from higher-level cognitive effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…sensory phenomenon (see [1][2][3][4]), it has been suggested that reference repulsion could arise owing to higher-level cognitive effects ( [5]; see also electronic supplementary material, discussion in [6]). That interpretation suggests that subjects have a veridical representation of the sensory stimulus at encoding and decoding in intermediate representations and that the bias arises from cognitive influences that are subsequently applied to them (as an example, see [16]).…”
mentioning
confidence: 99%
“…As was already noted by Mather (1980), the "classical" model would predict two simultaneously present MAEs opposite to the two adapting directions. Mather proposed an alternative model, called the "distribution shift model" (Mather, 1980;Mather & Moulden, 1980). In contradistinction to Sutherland's ratio model, in which only the activity of oppositely tuned motion detectors is compared, the distribution shift model takes the activity of all motion detectors with all direction preferences into account.…”
Section: Framework For Reasoning About the Maementioning
confidence: 99%